ReiseSchreiben. Potsdamer Vorlesungen zur Reiseliteratur - Ette, Ottmar (De Gruyter, 2020)
The volume systematically presents the genre of travel literature in historical perspective and its broad relevance for contemporary societies. It examines the historical, economic, social, and political backdrops of travel. The focus of the lectures is on French, Spanish, and Italian speaking travelers along with German and English travel literature from the early modern period to the 20th and 21st centuries.